A meta-analysis of microRNAs expressed in human aerodigestive epithelial cultures and their role as potential biomarkers of exposure response to nicotine-containing products. (2020) - Sewer, Alain; Zanetti, Filippo; Iskandar, Anita R.; Guedj, Emmanuel; Dulize, Remi; Peric, Dariusz; Bornand, David; Mathis, Carole; Martin, Florian; Ivanov, Nikolai V.; Peitsch, Manuel C.; Hoeng, Julia
Graphical abstract: Highlights: This meta-analysis evaluated 12 miRNA expression datasets from aerodigestive tissues. Treatments included cigarette smoke (CS) and reduced-risk product (RRP) aerosol exposure. Tissue-dependent changes were observed following CS exposure. Four miRNAs were identified as potential biomarkers of CS exposure response. Exposure to RRP aerosols resulted in reduced expression alterations relative to CS. Abstract: The expression of some microRNAs (miRNA) is modulated in response to cigarette smoke (CS), which is a leading cause of major preventable diseases. However, whether miRNA expression is also modulated by the aerosol/extract from potentially reduced-risk products is not well studied. The present work is a meta-analysis of 12 in vitro studies in human organotypic epithelial cultures of the aerodigestive tract (buccal, gingival, bronchial, nasal, and small airway epithelia). These studies compared the effects of exposure to aerosols from electronic vapor (e-vapor) products and heated tobacco products, and to extracts from Swedish snus products (in the present work, will be referred to as reduced-risk products [RRPs]) on miRNA expression with the effects of exposure to CS or its total particulate matter fraction. This meta-analysis evaluated 12 datasets of a total of 736 detected miRNAs and 2775 exposed culture inserts. The t-distributed stochastic neighbor embedding method was used to find similarities across the diversity of miRNA responses characterized by tissue type, exposure type, and product concentration. The CS-induced changes in miRNA expression in gingival cultures were close to those in buccal cultures; similarly, the alterations in miRNA expression in small airway, bronchial, and nasal tissues resembled each other. A supervised clustering was performed to identify miRNAs exhibiting particular response patterns. The analysis identified a set of miRNAs whose expression was altered in specific tissues upon exposure to CS ( e.g., miR-125b-5p, miR-132-3p, miR-99a-5p, and 146a-5p). Finally, we investigated the impact of RRPs on miRNA expression in relation to that of CS by calculating the response ratio r between the RRP- and CS-induced alterations at an individual miRNA level, showing reduced alterations in miRNA expression following RRP exposure relative to CS exposure (94 % relative reduction). No specific miRNA response pattern indicating exposure to aerosols from heated tobacco products and e-vapor products, or extracts from Swedish snus was identifiable.